PENGEMBANGAN MEDIA VIDEO PEMBELAJARAN BERBANTU APLIKASI CABRI 3D V2 TERHADAP PEMAHAMAN KONSEP KUBUS DAN BALOK KELAS VIII SMPIT INSAN MULIA - Fhela Vhantoria Ningrum; Karsoni Bertadinata; Muhammad Rafi Sundarta (Eksponen, 2023)
The lack of use of learning media to illustrate abstract forms into concrete forms, makes students less understanding of the concepts in cube and block material. This study aims to develop learning media with the help of the Cabri 3D v2 application for understanding concepts in the material of cubes and blocks for class VIII SMP. This study uses the development method belonging to Sugiyono (2017), this research limits its stages only to stage 5, namely until the product revision stage I. After conducting research and development of Cabri 3D v2 assisted learning media, the results are as follows: 1) material experts get percentages 86.66% in the "Very Eligible" category, 2) media experts get 82.22% in the "Very Eligible" category, 3) linguists get 91.42% in the "Very Eligible" category, 4) education practitioners get the result is 100% in the "Very Feasible" category, student responses get a result of 82% in the "very feasible" category. Based on the results of the research, it can be concluded that Cabri 3D v2 assisted learning media for understanding the concept of cubes and blocks material for class VIII SMP, is suitable for use as a learning medium to be able to support the learning process at school